2017
DOI: 10.3390/mi8090261
|View full text |Cite
|
Sign up to set email alerts
|

Application of Ultra-Small Micro Grinding and Micro Milling Tools: Possibilities and Limitations

Abstract: Current demands for flexible, individual microstructures in high quality result in high requirements for micro tools. As the tool size defines the minimum structure size, ultra-small tools are needed. To achieve tool diameters of 50 µm and lower, we investigate the complete manufacturing chain of micro machining. From the development of the machine tools and components needed to produce and apply the micro tools, the micro tools themselves, as well as the micro machining processes. Machine tools are developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 27 publications
0
11
0
1
Order By: Relevance
“…Relative to the tool substrate diameter, a grit size of 5-10 μm is a large grit size, beneficial in terms of tool life and easier to analyze post process. A previous study showed that it is the largest grit size to continually achieve a good grit density on the bottom surface of the tool when using electroless plating for the given tool substrate diameter [21].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Relative to the tool substrate diameter, a grit size of 5-10 μm is a large grit size, beneficial in terms of tool life and easier to analyze post process. A previous study showed that it is the largest grit size to continually achieve a good grit density on the bottom surface of the tool when using electroless plating for the given tool substrate diameter [21].…”
Section: Methodsmentioning
confidence: 99%
“…This MWF was compared with dry machining and experiments with distilled water as a coolant. The experiments conducted with SDS were the only ones where the tool managed to machine the assigned cutting path of 0.5 mm [15]; however, the tools suffered from high amounts of adhesions and flattened abrasive grits, indicating high process temperatures [21]. In a follow-up study, an SDS solution, isopropanol, and the commercially available synthetic oil DiaMond 80 were used via MQL in a micro milling experiment.…”
Section: Introductionmentioning
confidence: 99%
“…The continuing trend toward smaller feature sizes in micro-milling with higher precision and accuracy has led to demands for higher quality microtools, as the cutting tool edge radius defines the minimum UCT [ 139 ]. It was shown by Kirsch et al [ 140 ] that the material specifications of tool blanks highly influenced the quality and application of ultra-small microtools in the range of 4–50 µm. Generally, microtools are manufactured via grinding operations following the famous procedure by Aurich et al [ 141 ] for the design and machining of single-edge micro end mill tools with diameters between 10 µm and 50 µm and a variable helix angle.…”
Section: Process Inputsmentioning
confidence: 99%
“…Table 1. Electroless-plating solution composition [20]. The abrasive grits are whirled up in the coating solution via a magnetic stirrer.…”
Section: Micropencil Grinding Toolsmentioning
confidence: 99%